Testing Liquidity Persistence Among Firm-Specific and Macroeconomic Factors During Periods of Economic Instability in Egypt Using GMM Estimation - Elfaham, Karim (The Arab Journal of Administration, 2025)
The study focuses on measuring liquidity persistence among other internal and external determinants of liquidity for Egyptian non-financial listed firms during the period (2012-2022) using the Generalized Methods of Moments (GMM) to account for potential unobservable heterogeneity and endogeneity problems that might result from including lagged dependent variable among regressors. The results of the study confirmed the strong persistence of liquidity over the sample period. The results also highlighted positive significant effects of profitability, leverage, and growth of sales on liquidity. While inflation is proved to negatively affect liquidity over the sample period. Therefore, the current study further contributes to the existing body of literature though using the GMM estimation to test for the dynamic nature of the model of firm liquidity determinants. The results of the estimated model confirmed the significance of the lagged dependent variable among other firm-specific and macroeconomic determinants of liquidity. This interesting result highlights the impact of past values of liquidity on future values which refers to the ability of the sample firms to maintain stable liquidity levels over time. This outcome is consistent with the principles outlined in the Agency Theory. Moreover, the estimated model took into consideration the effects of external events during the sample period, which were proved to have insignificant effect on the estimated model.